The Effect of Motivation and Entrepreneurial Knowledge on Entrepreneurial Interest with Entrepreneurship Education as an Intervening Variable - Adhy Firdaus; Gamar Al Haddar; Yenik Pujowati; Soussou Raharimalala; Bambang Bambang (Pinisi Journal of Entrepreneurship Review, 2023)
This study aims to determine the effect of motivation and knowledge on entrepreneurial interest in Universitas Negeri Makassar students with entrepreneurship education as an intervening variable. The study will use a quantitative approach with a survey method. The research population is all entrepreneurship students of the Faculty of Economics and Business, Universitas Negeri Makassar which amounted to 427 students. Data collection was carried out using a questionnaire and later calculated using the Slovin dai with a sample size of 85 (eighty-five) respondents or 20% of the total population. The findings of this study indicate that motivation and knowledge have a significant role in shaping entrepreneurial interest through entrepreneurship education. Individual motivation, whether sourced from personal passion, career goals, or the drive to create change, can be a strong driver to develop entrepreneurial interest. Entrepreneurship education provides a foundation of knowledge and practical skills that strengthen this motivation. With the knowledge gained through education, individuals can understand the aspects of entrepreneurship, identify opportunities and overcome business challenges. The combination of high motivation and solid entrepreneurial knowledge creates a favorable environment for the development of entrepreneurial interest.